Evaluasi dan Perancangan User Interface untuk Meningkatkan User Experience menggunakan Metode Human-Centered Design dan Heuristic Evaluation pada Aplikasi Ezyschool - Ikrima Nuha Arifin; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
EzySchool is an application that is intended for parents of students to control the student activities at school. EzySchool has been developed since 2017. Although the EzySchool's User Interface (UI) design is good enough, it needs to be evaluated so that usability aspects are in accordance with User Experience (UX) principle well and correctly. Evaluation is done for determining the success rate of applied UX to meet user needs and satisfaction. The purpose of this study are to find usability problems based on heuristic principles and designing the solution design based on evaluator suggestions, severity ratings and Google Material Design (guidelines). The Human-Centered Design (HCD) approach was used because the design development approach and interactive system focus on the user and user needs. The Heuristic Evaluation (HE) method was used to find and assess usability problems based on heuristic principles with the help of experts as evaluators. The initial data collection was carried out by conducting interviews with EzySchool stakeholder regarding the analysis of the application usage context. Initial heuristic evaluation (involving 3 evaluators) produced 17 problems as a baseline for user needs to design a solution design. Iterate have been done once because of time limitness. The results of this study are a comparison between the initial evaluation and solution design results along with better solution design in UX which is indicated by a decrease of 10 heuristic problems so that only 7 problems were found in the solution design.